EEG neurofeedback in active athlete students : a methodological approach - Domingos, Christophe dos Santos (2020)
Neurofeedback training is a recent technique in sport and the protocols for its application in improving sports performance are based largely on existing protocols in non-athletic populations or there is still not enough robustness to be a valid protocol for safe replication. Based on this existing gap, several protocols increasing the individual alpha band were proposed to improve performance in active and athlete students. In addition to the protocols, it was also proposed to verify the behaviour of the other frequency bands during the increase of the individual alpha band training and if the effects persist after one month of the last training session. This dissertation is composed of four studies where three of these studies were based on the best protocols to be applied (the first one tried to understand if the effects of a protocol performed to a non-athletic population would be equal when submitted to an athletic population, the second one tried to figure out which was the best weekly training frequency to attain the best results, and the third one sought to understand whether the place where the collection were performed, conditioned the final results) and were submitted to peer-reviewed journals. The fourth study is divided into two minor studies (one that demonstrates the behaviour of the other frequency bands during training and another that tries to see if the effects persist after a month). The total sample was 74 subjects (60 active or athlete students and 14 sedentary). Each study was conducted on 30 active or athlete students over 5 to 8 weeks of a supervised neurofeedback training and were composed of an experimental group and a control group. Exception for study 1 where the sample consisted of 45 subjects (two experimental groups and a control group) and had a duration between 8 to10 weeks. There were 12 training sessions that consisted of 25 min. It was verified that the active or athlete students had different results from the sedentary when applied the same protocol (study 1), the most frequent protocol is the one that has better results compared to all the other protocols (study 2) and that to carry out sessions in an environment with intermittent noise or without noise does not present differences in active or athlete students (study 3). Additionally, it was verified that the less frequent bands tend to increase with the training and the opposite occurs with the most frequent bands. It was also concluded that individual alpha band training and performance testing persist after one month.